PENDAMPINGAN OLEH TIM KELOMPOK KERJA AKADEMISI DALAM PENENTUAN FOKUS KAJIAN INFRASTRUKTUR DI KOTA MEDAN - Cut Nuraini; Rizky Franchitika; Yudha Hanova; Surta Ria Nurliana Panjaitan; Muhammad Amin (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
The scientific study of the integrated utility network in the city of Medan, and the mapping of safety locations in the city of Medan. The title of the study became the initial discussion material to formulate the focus of research in the infrastructure sector on the most urgent (important) infrastructure problems found in the city of Medan inventory of drainage flow dimensions and patterns, Measurement of drainage channel base elevation, Inventory of public perceptions of water management and drainage systems, Analysis of hydrology Hydraulic analysis and social analysis of society. It was found that there were 2 sewers on Jalan Cempaka, but the dimensions that changed significantly resulted in being unable to accommodate runoff from upstream. The sewer at the District Office is at the lowest elevation and becomes a collection of flows from various directions. The second sewer near the leafy Glugur road is suffering from the settlement. The impact of land-use change without knowing the function of the natural channel has an impact on the closure of the natural discharge channel, thus affecting the pattern of runoff. Selayang River is one of the causes due to the low channel dimensions. Irregular channel size is related to flooding problems due to river overflow, it is necessary to normalize the river by considering the potential that exists in each river. Flood problems also require handling from upstream to downstream. Solving the problem of air and flood problems requires clear regulations. For this reason, appropriate regulations are needed for solving water and flood problems at the level of policies or regulations of the Medan City Government.Keywords: Accompaniment, Network research, development, infrastructure,